MOTIVASI TERHADAP PEMBENTUKAN KARAKTER TOKOH UTAMA DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Nia Heldina Ramon Heldina Ramon; Elmustian Rahman Rahman; Hadi Rumadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study aimed to motivation of the main character of the formation contained in the state’s novel Negeri Lima Menara by Andrea Hirata. The theory used in this research is divied into to theories of motivation, namely, internal and external motivation. The method used in this study is descriptive, in get a picture of a state that lasts and not only to collect, analyze, and organize data, but must be inferred as an attempt to discover the meaning of the research result that have been achieved so that the expected result of this descriptive method of research on internal motivation and external main character of the formation could be interpreted as meaning a novel. Data analysis as carried out on the main character in the Laskar Pelangi novel by Andrea Hirata. Description motivation were examined in this study indicate how about the internal motivation and external lead character can shape his personal character. This study is expected to provide benefits for the reader to understand the description of the motivation motivation is divided into two, namely, internal and external motivation. This is done to increase the wealth of the inner reader in appreciating literature especially novel. Keywords: motivation internal, external, character